1998
DOI: 10.1002/(sici)1097-4636(199805)40:2<324::aid-jbm18>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of titanium surfaces for covalent attachment of biological molecules

Abstract: Abstract:The surface of implantable biomaterials is in direct contact with the host tissue and plays a critical role in determining biocompatibility. In order to improve the integration of implants, it is desirable to control interfacial reactions such that nonspecific adsorption of proteins is minimized and tissue-healing phenomena can be controlled. In this regard, our goal has been do develop a method to functionalize oxidized titanium surfaces by the covalent immobilization of bioactive organic molecules. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
245
0
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(264 citation statements)
references
References 0 publications
13
245
0
6
Order By: Relevance
“…The most common ones use silane coupling agents that react with the oxide layer formed on metal surfaces. [21][22][23][24][25][26][27] In most cases, the silane coupling agent consists of a trimethoxy or triethoxy silane where the fourth bond of the silane molecule is an organo-functional group that can be further reacted to attach a variety of organic compounds or polymers. The methoxy or ethoxy groups hydrolyze, leaving the silanol to react with the metal oxides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common ones use silane coupling agents that react with the oxide layer formed on metal surfaces. [21][22][23][24][25][26][27] In most cases, the silane coupling agent consists of a trimethoxy or triethoxy silane where the fourth bond of the silane molecule is an organo-functional group that can be further reacted to attach a variety of organic compounds or polymers. The methoxy or ethoxy groups hydrolyze, leaving the silanol to react with the metal oxides.…”
Section: Introductionmentioning
confidence: 99%
“…These metal-O-Si bonds in and of themselves are not strong and may hydrolyze in water; however, the use of trimethoxy or triethoxy functional groups leads to a polymer network with multiple attachment points to the metal, thus securing the attached silane layer. 21,28 Nanci et al 23 did studies on the aqueous stability of silanized Ti and showed that, after a small initial decrease, the elemental concentrations of the various components of the amino silane remained constant up to 168 h. Puleo has shown that trypsin retained its enzymatic activity when immobilized on Ti and Co alloys via a ␄-aminopropyltriethoxy silane. 24,29 Further studies revealed that this enzymatic activity was retained for up to 96 h in standard cell culture.…”
Section: Introductionmentioning
confidence: 99%
“…The surface of material can change with time, and is often distinctly different from the bulk properties, because of oxidation and contamination. Although the surface clearly plays an important role in implant/cell interactions, the relationships between surfaces of the implant, its reactivity with tissue constituents, and long-term integrity and clinical efficacy are still poorly understood [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] The rationale for using H 2 SO 4 /H 2 O 2 to nanotexture metals was to permit simultaneous etching and oxidation of the surface in a controlled manner. 29 This method is effective, but the range of nanoporosity achieved so far is narrow. In this paper, we introduce five new bicomponent reagents for nanotexturing, which extend the range of surface modifications that can be achieved by simple chemical oxidative etching.…”
mentioning
confidence: 99%